Star-hexagon transformer and non-isolated three-leg VSC based three-phase four-wire DSTATCOM. (21st August 2009) - Singh, Bhim; Jayaprakash, P.; Kothari, D.P.
A new three-phase four-wire DSTATCOM (distribution static compensator) is proposed for power quality improvement in the distribution system. The DSTATCOM is based on a star/hexagon transformer and three-leg VSC (voltage source converter). It compensates harmonic current, reactive power and balances the load along with neutral current compensation. Each of the three single phase transformers has three windings and the secondary windings are connected in star/hexagon configuration for interfacing to a three-phase four-wire power distribution system. The IGBT (insulated gate bipolar transistor) based VSC is a capacitor supported and it is controlled for the required compensation of load currents. The DC bus voltage of the VSC is regulated even during dynamic load variations. The DSTATCOM is tested for power factor correction and voltage regulation along with neutral current compensation, harmonic elimination and load balancing under linear loads as well as non-linear loads. The performance of the three-phase four-wire DSTATCOM is validated using MATLAB software with its Simulink and SimPower System (SPS) tool boxes.